ALUR NOVEL KEINDAHAN DAN KESEDIHAN KARYA KAWABATA YASUNARI - Novi Andari; Eva Amalijah (Universitas 17 Agustus 1945 Surabaya, 2018)
Abstract. Appreciating the work of fiction by understanding the plot is a very important activity because every stage of the plot actually contained all the elements of fiction that make up the work. The object of the research used is the work of fiction in the form of one of Kawabata Yasunari's novels, Beauty and Sadness. Kawabata Yasunari's works are famous to be not easily understood and interpreted (Rosidi, 1989: 74) .Semi (1991: 68) added that to be able to interpret a literary work, the reader can analyze only some certain desired components. Therefore, this study analyzes only one component of the plot. The purpose of research is to interpret the literary work of Beauty and Sadness novel through the plot factor along with the aspects contained in the plot. The result of the research shows that: 1) the event of this novel is real and fantasy, functional, subject, and event of connection and reference; 2) there are 9 episodes as functional events; 3) there are 6 stages of the plot which is the beginning, the dispute, the complexity, the peak, and the end; 4) the type of plot is the double plot (quantity), the tight plot (quality), forward / progressive plot (sequence of separation), ascending plot (tension), open / no ending plot (the end of the story). Keywords: Fiction work, novel, intrinstic, plot